Two new species of Isometopus Fieber (Hemiptera: Heteroptera: Miridae: Isometopinae) and a key to all known species of the genus in Europe and the Middle-East - Akingbohungbe, A. E. (Zootaxa, 2012)
Isometopus gharaati n. sp. and I. praetermissum n. sp. are described as new species from the Middle East and southernEurope. Isometopus praetermissumbelongs in the subgenus Isometopus Fieber whereas I. gharaati belongs in the subge-nus Jehania Distant; and with their description, the number of known species for the genus Isometopus Fieber in Europe and the Middle East is now ten. A key for separating all these species is presented.